Climate Change and Sports: Global Impacts on Athletes, Events, and Infrastructure - Kim, Seohyun (Technium Sustainability, 2025)
Climate change is not only an environmental and socio-economic challenge but also a public health and institutional issue with direct ramifications for global sport. From the health of athletes to the degradation of infrastructure, sport is both a victim of climate instability and a contributor to climate change. This study organizes the impacts of climate change on sport into four interconnected domains: (1) athlete health and safety, (2) interruptions in competition and scheduling, (3) infrastructure vulnerability and water resource scarcity, and (4) the role of sport in adaptation and activism. To engage with these topics, this analysis incorporates literature and policy reviews, case studies, and R-based quantitative modelling. The climate and weather data were sourced from the ERA5 Reanalysis (ECMWF) and the Global Historical Climatology Network (NOAA) datasets and incorporated with sport performance and injury surveillance data, sourced from the Sports Reference archives, NCAA and CDC injury data, and climate impact surveys reported by athletes through World Athletics. In addition, projections from Climate Central and the Union of Concerned Scientists are included, highlighting the risks posed by extreme heat events to athletes, spectators, and infrastructure. By synthesising all of these interdisciplinary data sources, the manifestations of systemic susceptibility to climate instability within the global sports ecosystem can be demonstrated, alongside the critical imperative for integrated climate resilience planning across sport.